Compositional Differences between Preterm Milk of Different Gestational Ages with the Term Milk: A Comparative Lipidomic Study by LC‐MS/MS - Zhao, Ying‐chun; Zhang, Ying; Liu, Chun‐xue; Yan, Dong‐yong; Dong, Ping (European journal of lipid science and technology, 2022)
Human milk lipids have important biological effects on recipient infants. The objective of this study is to comprehensively describe lipidomic differences between preterm milk of different gestational ages and term milk over the course of lactation. Colostrum (<5 d postpartum, n = 20 for very preterm [VPT], n = 20 for moderately preterm [MPT] and n = 30 for full‐term [FT]) and mature milk (at four weeks postpartum, n = 11 for extremely preterm [EPT], n = 23 for VPT, n = 21 for MPT, and n = 25 for FT) are collected from 88 mothers who had delivered premature babies and 39 who had delivered term infants. It is found that the relative abundance of 10 out of 43 lipid subclasses are persistently higher in preterm milk than in term milk over the course of lactation. Diacylglycerol and fatty acid ester of hydroxyl fatty acid (FAHFA) lipid classes contribute most to the differences. The ten individual lipid species differing most significantly between VPT and FT colostrum are mainly part of the phosphatidylethanolamine and diacylglycerol groups. Levels of lipid species from the FAHFA class are significantly higher in both EPT and VPT mature milk than in their FT counterpart. The lipids in preterm and term milk show substantial differences, which may be critical for postnatal growth. Practical applications: These findings expand the current understanding of lipid components in human milk and provide important laboratory data for the future management of infant feeding, particularly of fragile, high risk EPT and VPT infants. The present study identified documenting changes in the relative abundance of lipids in preterm and term milk. For the first time, it is found that the levels of fatty acid ester of hydroxyl fatty acid (FAHFAs, which is a newly discovered lipid family that exist in the human body) in preterm milk at different gestational age are significantly higher than that in term milk.